If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4x + 8) + -6 = 0 Reorder the terms: 9(8 + 4x) + -6 = 0 (8 * 9 + 4x * 9) + -6 = 0 (72 + 36x) + -6 = 0 Reorder the terms: 72 + -6 + 36x = 0 Combine like terms: 72 + -6 = 66 66 + 36x = 0 Solving 66 + 36x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-66' to each side of the equation. 66 + -66 + 36x = 0 + -66 Combine like terms: 66 + -66 = 0 0 + 36x = 0 + -66 36x = 0 + -66 Combine like terms: 0 + -66 = -66 36x = -66 Divide each side by '36'. x = -1.833333333 Simplifying x = -1.833333333
| 2x+3x=4x-4 | | (3+5)(2m-8)=0 | | 4x4y3/12x1y2 | | 6(12)+6n-70-4n=8 | | 22613.85=x+(x*.0825) | | 4x+9=-20 | | 23h-67=-44 | | (12x-6)+(16-5x)= | | 12x+3y+120=180 | | 7-4.5= | | 3(2r+6)=24 | | 9(2x+6)= | | 5d-c=12 | | 8(9x+9)+9(11-x)= | | (4x+1)+(11-4x)= | | 35+50x= | | (4x+13)+(8x-5)= | | 7(8x+5)= | | 3x-5x=-9+x | | 2x^4+7=47 | | 2a+7b-3b+a= | | m+50x=35 | | f(x)=-16x+160x | | 6x+x-8=6x+5 | | 3.2=125x | | 8m-2m=72 | | 5g-5=7 | | -5=-19-n/7 | | 13x-60=83 | | x^6+7x^5+2x^4+9x^3+10x^2-12x-15=0 | | 2/5(x-15)=500 | | c/7+5=-6 |